2008
DOI: 10.1073/pnas.0801864105
|View full text |Cite
|
Sign up to set email alerts
|

Protein folding: Independent unrelated pathways or predetermined pathway with optional errors

Abstract: The observation of heterogeneous protein folding kinetics has been widely interpreted in terms of multiple independent unrelated pathways (IUP model), both experimentally and in theoretical calculations. However, direct structural information on folding intermediates and their properties now indicates that all of a protein population folds through essentially the same stepwise pathway, determined by cooperative native-like foldon units and the way that the foldons fit together in the native protein. It is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 62 publications
3
38
2
Order By: Relevance
“…In respect to the suggestion that proteins may fold through a number of alternative, independent, parallel routes, we have shown that the kinetic complexity observed in such spectroscopic studies can be explained with fewer fitting factors and equivalent or better χ 2 fit by a single pathway in which a probabilistic barrier insertion affects some fraction of the population and not another (26,27). Given only kinetic phase data and no structural information, it is not possible to distinguish a multiple pathway interpretation from a single pathway with an optional barrier that slows one population fraction and not another (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In respect to the suggestion that proteins may fold through a number of alternative, independent, parallel routes, we have shown that the kinetic complexity observed in such spectroscopic studies can be explained with fewer fitting factors and equivalent or better χ 2 fit by a single pathway in which a probabilistic barrier insertion affects some fraction of the population and not another (26,27). Given only kinetic phase data and no structural information, it is not possible to distinguish a multiple pathway interpretation from a single pathway with an optional barrier that slows one population fraction and not another (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Given only kinetic phase data and no structural information, it is not possible to distinguish a multiple pathway interpretation from a single pathway with an optional barrier that slows one population fraction and not another (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a dearth of experimental verification, this view is still current, and experimental as well as theoretical folding results are often phrased in this language. Some spectrometry-based experiments have been taken to suggest more than one folding pathway (55-59), but it has been shown that this kind of data cannot distinguish alternative parallel pathways from a given pathway with alternative misfolding barriers (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Additional work is needed to discriminate the mutual effects of the driving force (which could be defined as the derivative of the free energy relative to a generalized folding coordinate) from trapping forces (derivatives of the free energy relative to local degrees of freedom) in folding. The trapping forces can contribute to the kinetic heterogeneity of protein folding and be a source of optional misfolded errors in the mechanism of predetermined folding pathways recently proposed (34). The methodology developed here to discriminate slow and fast residues by analyzing their MSD could be useful to analyze folding.…”
Section: Dynamics In a Multiple-minima Potential And Varying Conformamentioning
confidence: 99%